2019
DOI: 10.1088/2053-1591/ab29cc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the dopant on the structural and hyperfine parameters of Sn0.95M0.05O2 nanoparticles (M: V, Mn, Fe, Co)

Abstract: To cite this article: V Bilovol et al 2019 Mater. Res. Express 6 0850h6 View the article online for updates and enhancements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This conclusion is in perfect agreement with X-ray photoelectron spectroscopy performed in Sn 1– x V x O 2 ( x : 0.01, 0.03, and 0.05) nanoparticles synthesized by the combustion synthesis method that revealed the presence of vanadium as V 4+ species in the SnO 2 host lattice . A similar result was reported in ref for other V-concentrations.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This conclusion is in perfect agreement with X-ray photoelectron spectroscopy performed in Sn 1– x V x O 2 ( x : 0.01, 0.03, and 0.05) nanoparticles synthesized by the combustion synthesis method that revealed the presence of vanadium as V 4+ species in the SnO 2 host lattice . A similar result was reported in ref for other V-concentrations.…”
Section: Resultssupporting
confidence: 91%
“…SnO 2 is a material that can be easily doped with a variety of impurities, and it was shown that the properties of SnO 2 nanostructures can be handled by doping it with adequate impurities. , SnO 2 nanoparticles have been successfully doped with transition-metal ions (V, Fe, Co, Mn, and Cu). In particular, V-doping is expected to have significant effect on optical response ,, of SnO 2 (the name “vanadium” is originated in the mythological Scandinavian god Vanadis because of its multicolored compounds), its electronic and catalytic properties, , and it can induce a ferromagnetic response at high temperature. ,,, …”
Section: Introductionmentioning
confidence: 99%